New Can Bus Communication Modules for Digitizing Forest Machines Functionalities in the Context of Forestry 4.0 - Geoffrey Spencer; Pedro M. B. Torres (IEEE Access, 2023)
In line with the context of Industry 4.0, forestry, and in particular the entire ecosystem around it, also needs digitalization solutions in order to allow better interaction between all agents that work and live from the forest. It is important for a better management of forest resources allowing productivity gains, more sustainability and resilience. One of the agents that can benefit, but also contribute to better forestry, are machine producers. With digitalization, the machinery is now equipped with new and better sensors that can be used not only for machine operations but also for forest management, through LiDAR (Light Detection And Ranging) or RGB (Red, Green, Blue) cameras for example. On the other hand, there are new needs for predictive maintenance or solutions for remote assistance of machines operating in the forest, typically in isolated areas with great limitations in access to communications. Thinking about these technological challenges, this work seeks to provide answers with communication solutions in forest machines, enabling the digitalization of functionalities, also allowing remote access to machine controllers in order to provide them with connectivity in an IIoT (Industrial Internet of Things) scenarios. New hardware modules designed in partnership and according to the prerequisites of a forest machine manufacturer are presented. These modules are a step towards digitizing the machines and opening up the scalability of new requirements, as well as remote access through additional gateways. The results already obtained in real scenarios show that these modules can be a concrete solution for the current and emerging needs of industrial machine manufacturers.